English Language Minority in Indonesian EFL (English Foreign Language) Learners Rural Area - Haris Mulyanto; Encik Shahzool Hazimin Bin Azizam; Jailani Jusoh (International Journal of English and Applied Linguistics (IJEAL), 2023)
English as a communication tool has been vital aspect into worldwide society. The element of English has a more profound influence through the implementation of life and daily human habit. Nowadays, English has been normalized as a language necessity for academics, basic internet norms, social status, and business. Hence, it is standard for English as a requirement for many fields. Although the fact that society uses English as language instruction, there is a majority of Indonesian districts that could not be able to apply the language vice versa. It is due to internal and external factors such as geographic area, difficulty, and national curriculum design. Consequently, it created imbalance of education distribution aspect and rights. Therefore, this research elaborates and finds out the minority elements of English language involved in EFL learners in rural area. The primary method of inquiry in this research is a literature review which means the technique intended to gain a collection of previous research from the journal, internet, book, and the latest research. The data were analyzed, synthesized into a findings unit, and elaborated on how to broaden the result to be discursive.